PENGARUH LEADERSHIP DAN COMPENSATION TERHADAP JOB PERFORMANCE KARYAWAN SWISS-BELINN HOTEL MEDAN - Juliana, Juliana; Djakasaputra, Arifin (www.bsi.ac.id, 2019)
Abstract – The purpose of study to analyze the effect of leadership and compensation on job performance The study population was 100 employees of Swiss-belinn Hotel Medan. The data collection method is carried out by distributing questionnaires to 100 respondents. The sampling technique used is non probabilty sampling. The data analysis technique used is the validity and reliability test, and the hypothesis.The results showed that there was an influence of leadership and compensation on job performance of employees of Swiss-belinn Hotel Medan.Key Word: leadership,compensation and job performance